Стратегия создания отпочковавшихся инновационно-активных предприятий (Путеводитель предпринимателя, 2020)
Strategy of creation of the spin-off companies at realization of innovative potential regional is innovative-industrial clusters is considered. Advantages and process lacks «spin-off» small enterprises are defined.